Intellectual property protection: An emphasis on plant varieties - DATT, SHIV; SINGH, VIKRAM; SHARMA, P K; SAXENA, SANJEEV (The Indian Journal of Agricultural Sciences, 2023)
The enactment of Intellectual Property protection laws globally and involvement of private seed industry in India had become indispensable for protection of IP in agriculture as whole and plant varieties in particular. For protection of plant varieties, the Distinctiveness Uniformity and Stability (DUS) descriptors of various crops (vegetables, field crops, floriculture, horticulture crops, etc.) were developed and notified by the Protection of Plant Varieties and Farmers Rights (PPV and FR) Registry for testing. With increasing awareness of IPR in agriculture, the submission of applications of plant varieties from the notified crops for registration has started for protection under the Registry. Subsequently, public sector (Indian Council of Agricultural Research (ICAR) and Agricultural Universities (AUs)); private sector; and farmers started submission of Extant, New and Essentially Derived Varieties (EDVs) applications in the notified crops. The study period pertaining to years 2007-2015 reveals that public sector has contributed immensely in protecting plant varieties of self-pollinated crops (food, fibre and pulses crops), whereas the private sector’s focus is largely confined towards open-pollinated varieties. Private sector has submitted highest number of ‘EDVs’ of tetraploid cotton. Progress in farmers’ varieties for protection under PPV and FRA reinforces the importance and uniqueness of this sui generis system adopted by India. It is, expected that the prospects of variety and seed development sectors will improve overtime. This trend also opens the scope for the plant breeders to design varietal development programmes for desirable traits in various crop species.